The antigenic determinant that defines thymic nurse cells is expressed by thymic epithelial progenitor cells - Chilukuri, Rajendra V. E.; Patel, Viral K.; Martinez, Marcia; Guyden, Jerry C.; Samms, Michael D. (Frontiers in Cell and Developmental Biology, 2014)
Stromal thymic epithelial cells with the multicellular structure unique to thymic nurse cells (TNCs) express the pH91 antigen on their cell surfaces. The multicellular TNC-complexes develop through an intimate association between αβTCR+CD4+CD8+ thymocytes and pH91-expressing cortical epithelial cells. TNCs participate in MHC-restriction and exhibit epithelial cell progenitor characteristics. In this report, we show that as early as E11.5 stage of thymus development, the pH91 antigen is expressed in association with K8, K5, Foxn1 and p63. The expression of these epithelial progenitor markers along with the pH91 antigen persists throughout thymic development in the murine thymus. At E13.5, pH91+ cells express relatively low levels of MHC class II. After E17.5, the first multicellular TNC complexes are recognizable along with increased cell surface expression of MHC class II. Our data suggest that epithelial cells bearing the “progenitor phenotype” develop into the multicellular TNCs.